High-rise security and fire life safety - Craighead, Geoff (Butterworth-Heinemann/Elsevier, 2009)
High-Rise Security and Fire Life Safety, Third Edition, is a comprehensive reference for managing security and fire life safety operations within high-rise buildings. It spells out the unique characteristics of skyscrapers from a security and fire life safety perspective, details the type of security and life safety systems commonly found in them, outlines how to conduct risk assessments, and explains security policies and procedures designed to protect life and property. Craighead also provides guidelines for managing security and life safety functions, including the development of response p.